Accuracy of lung ultrasound and chest X-rays in diagnosing acute pulmonary oedema in patients presenting with acute dyspnoea in emergency department - Sanniya Khan Ghauri; Khawaja Junaid Mustafa; Arslaan Javaeed; Abdus Salam Khan (Journal of the Pakistan Medical Association, 2021)
To determine the diagnostic accuracy of lung ultrasound and chest X-ray in diagnosing Acute Pulmonary Edema (APE) in patients presenting with acute dyspnea in emergency department. This study was conducted at the emergency department of Shifa International Hospital, Islamabad from 31st July 2018 to 31st January 2019. A total of 225 patients presenting with dyspnoea and satisfying inclusion criteria were assessed by clinical examination, lung USG and chest X-ray. The results of chest X-ray and lung USG were compared with clinical diagnosis. The current study revealed sensitivity of chest X-ray and LUS ( 60.16% versus 91.05%), specificity (66.67% versus 91.18%), positive predictive value (68.52% versus 92.56%) and the negative predictive values (58.12% versus 89.42%) respectively. Present study revealed that the LUS has better accuracy than chest X-ray for diagnosis of APE. Continuou...